Premortem interventions in dying children to optimise organ donation: an ethical analysis - Brierley, Joe (Journal of medical ethics, 2016)
A range of interventions in dying patients can improve both the possibility of successful organ donation and the likely long-term success of transplantation. The ethical and legal issues surrounding such interventions, which most frequently occur in the context of donation after circulatory determination of death, are complex, controversial and many remain unresolved. This is true with adults, but even more so with children, where the issue of organ donation and premortem interventions to facilitate it, are highly sensitive. Essentially, such interventions are being undertaken in dying children who cannot medically benefit from them, though arguments have been advanced that becoming a donor might be in a child's extended best interest. However, certain interventions carry a potential risk, although small, of direct harm and of course overall objections to child donation after circulatory determination of death per se are still expressed in the literature. But, unlike the case in critically ill adults, those giving permission for such interventions are normally able to fully participate in decision-making, and indeed to consent, to both donation and premortem interventions. We review the issue of the use of premortem interventions in dying children to facilitate organ donation, including decision-making and ethical justification. Individual interventions are then considered, including an ethical analyse of their use. Finally, we recommend an approach using a combination of welfare checklist strategy, coupled with the establishment of an agreed zone of parental discretion about individual interventions which might be used in dying children to increase the possibility of successful organ donation.